2015
DOI: 10.26719/2015.21.6.389
|View full text |Cite
|
Sign up to set email alerts
|

Spatial accessibility of the population to urban health centres in Kermanshah, Islamic Republic of Iran: a geographic information systems analysis

Abstract: Geographic information systems (GIS) analysis has not been widely used in underdeveloped countries to ensure that vulnerable populations have accessibility to primary health-care services. This study applied GIS methods to analyse the spatial accessibility to urban primary-care centres of the population in Kermanshah city, Islamic Republic of Iran, by age and sex groups. In a descriptive-analytical study over 3 time periods, network analysis, mean centre and standard distance methods were applied using ArcGIS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 16 publications
3
25
0
1
Order By: Relevance
“…Therefore, the present study aimed to investigate inequality in access to medical care in the townships based in Kermanshah, Iran. The results of studying the status quo of the distribution of health resources in Kermanshah showed that there was heterogeneity in this regard, which was consistent with the results of studies stating that there were large gaps between different regions in Iran in terms of this factor [11,32,39,[43][44][45].In a study performed by , it was concluded that the factors such as lack of planning, wrong policymaking in terms of the distribution of health services, unfair distribution of financial resources and structural problems accounted for this situation [45].In addition, the consequences of the eight-year war between Iran and Iraq, economic sanctions, political-economic weaknesses, excessive population growth, and excessive migration of villagers to cities might account for this situation in Iran [46].Besides, the health status of people in various health issues, including diseases and other cases in Kermanshah will be negated by the lack of proper access to healthcare supplies [35,47]. In terms of the ratio of specialists to a population of 10,000 people, the results of the present study were indicative of an unequal distribution of facilities across the townships of Kermanshah Province.…”
Section: Figure 3 Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Therefore, the present study aimed to investigate inequality in access to medical care in the townships based in Kermanshah, Iran. The results of studying the status quo of the distribution of health resources in Kermanshah showed that there was heterogeneity in this regard, which was consistent with the results of studies stating that there were large gaps between different regions in Iran in terms of this factor [11,32,39,[43][44][45].In a study performed by , it was concluded that the factors such as lack of planning, wrong policymaking in terms of the distribution of health services, unfair distribution of financial resources and structural problems accounted for this situation [45].In addition, the consequences of the eight-year war between Iran and Iraq, economic sanctions, political-economic weaknesses, excessive population growth, and excessive migration of villagers to cities might account for this situation in Iran [46].Besides, the health status of people in various health issues, including diseases and other cases in Kermanshah will be negated by the lack of proper access to healthcare supplies [35,47]. In terms of the ratio of specialists to a population of 10,000 people, the results of the present study were indicative of an unequal distribution of facilities across the townships of Kermanshah Province.…”
Section: Figure 3 Discussionsupporting
confidence: 86%
“…The third step of this method was to calculate the human development which its value is between zero and one (the closer the obtained value to one, the more developed it will be [42].This was assessed by A) Mean Center: It is the mean of geographical latitude and longitude coordinates of all features within the scope of the study, and its calculation is appropriate for both tracking the changes in the spatial distribution of terrains and their comparisons. It is calculated as follows [11]:…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, the studies have shown that Kermanshah has many health problems. Such as HIV/AIDS [2,3,13,16], cancer [17], high fertility [18,19], mortality [20,21], low quality of life [22,23] and lack of proper access to health centers [24][25][26][27]. As a result, it causes many health problems in the city.…”
Section: Introductionmentioning
confidence: 99%